Recyclable waste Dry-cell batteries derived carbon dots (CDs) for detection of Two-fold metal ions and degradation of BTB dye - Annamalai, Kumaresan (Waste management (New York, N.Y.), 2023)
Copyright © 2023 Elsevier Ltd. All rights reserved.